PERANAN MEDIA BENDA NYATA ( MAKHLUK HIDUP ) DIVARIASIKAN DENGAN PAPAN GABUS DAPATMENINGKATKAN HASIL BELAJAR MATERI SPERMATOPHYTA ( TUMBUHAN BIJI) - Izzun Nadlah (Universitas Negeri Semarang, 2012)
Based on the data analyses problem in the SMPN 40 Semarang there low motivation, only was 35,7% active in the learning process, and the low of the study result indicate the lower quality of learning happened in the class VII A SMPN 40 Semarang in 2010/ 2011. That this cause there is no variation foam boart media andreal life materials media in the learning process interaction in the Spermatophyta. The problems of the classroom action reasearch was “Did application of variationfoam boartmedia andreal life materials media in the learning process is to improve the achievement learning about interaction in the Spermatophyta in the class VII A ?“. The goal of the car were to increase : 1. The learning process more then pull, (2) the learning process more then interctive, (3) the achievement of learning then more, (4) times efficient and energy. The subject topics wereGymnospermae and Angiospermae. The Car is held in three cycle : in VII A class with 32 students. The research revealed that the number of students who involve in scientific work from the I-III cycles were 68,5 %, 77,7% and 87% respectively. In the I-III cycle, the number of students who satisfied with the teaching learning process was 89,06 %, 90,70 % and 99 % respectively. The percentage teaher activity from the I-III cycle 66%, 78,8 %, 89.93 %. There were 75%, 81,25%, 93,75%, the students test result.